Tourists' perceptions of robots in passenger transport. (November 2021) - Webster, Craig; Ivanov, Stanislav
Abstract: In this article, the authors investigate the way that the public views automation technologies and their usage in tourist transportation based on data from a large-scale international survey. The authors explore the use of robots for the provision of information with regards to travel, the use of autonomous vehicles, and other robot-delivered transport-related tasks. The findings indicate that the perceived reliability, safety, and usefulness of the use of robots for transport play a major role in impacting perceptions of the appropriateness of using robots for different purposes. The findings also indicate that no demographic characteristics, apart from gender, seem to play any role in conditioning perceptions of the appropriateness of using robots in the field of transportation. Highlights: Robots are used for information provision, as autonomous vehicles, and other tasks. Reliability, safety, usefulness, (dis)advantages, and attitudes shape perceptions. The factors have different influence on the different groups of tasks.